AGAMA ANTARA KONFLIK DAN SOLUSI - Syapar Alim Siregar; Rahman Zulfadli Lubis (Lembaga Kajian Keagamaan Universitas Pamulang, 2022)
In religion there must be religious conflict. This religious conflict is actually a conflict between one religion and another. Conflict is as inherent as religious conflict. Religious conflict arises when religion exists and humans are always unable to escape negative stereotypes about other religions, so that religious conflicts arise. However, the conflict does not have a potential threat in itself, if this conflict can be handled with a better life, not in violence (threats). So, the main thing in resolving this conflict is really conflict processing through the use of the correct channel so that it does not arise. Every conflict resolution must be resolved according to the pillars and awareness of peace for each of these religions. Kata Kunci: Agama, Solusi, Konflik